Oxygen ionic transport in brownmillerite-type Ca2Fe2O5±d and calcium ferrite-based composites - Shaula, A. L.; Kolotygin, V. A.; Naumovich, E. N.; Waerenborgh, J. C.; Pivak, Y. V.; Kharton, V. V. (Видавництво Львівської політехніки, 2012)
The present work was centered on the studies of oxygen permeability, mixed conductivity, dilatometric behavior, crystal structure and microstructure of Ca2Fe2O5±d and Ca2(Fe,M)2O5±d (M = Co, Mn) solid solutions, and dualphase Ca2Fe2O5 – Ce0.9Gd0.1O1.95 composites. The anisotropic oxygen-ion diffusion in calcium ferrite lattice was simulated using molecular dynamics and atomistic modeling techniques. The computer simulations results were analyzed in light of the experimental data on ionic conduction and thermodynamic stability.
Keywords: oxide-ion diffusion; computer simulations; brownmillerite; oxygen permeation; dimensional stability